Corporate governance mechanisms and financial performance: evidence of quoted and unquoted firms in ghana - KEN-FRED CZAR (KNUST, 2024)
A thesis presented to the Department of Accounting and Finance, Kwame Nkrumah University of Science and Technology In Partial Fulfilment of the Requirement for the Award of Master of Science (Accounting and Finance)